Analisis Pengukuran Kinerja Unit Usaha Syariah Bank Sumut Medan dengan Pendekatan Mashlahah Performa - Miranda Julia Pasaribu; Siti Aisyah; Sugianto (Jurnal Penelitian Ekonomi Akuntansi, 2023)
This study aims to assess several aspects of the company's current value chain. Maslahah Performa is a performance measurement created by Achmad Firdaus, where the Maslahah Performa approach uses six measurement orientations used for sharia-based performance assessments that are in line with Islamic principles. This research is included in the descriptive case study category. The technique used in this study is the sharia economic approach which is used to determine whether a financial institution implements performance in accordance with sharia principles which is then complemented by a management approach. This study measures the performance of results and processes that are measured using quantitative data in addition to qualitative data to assess the effectiveness of maslahah owned by a company. Using descriptive statistics as a data analysis method used to examine quantitative data. The performance system with the maslahah performance approach is a spiritual leadership management system that is formulated using the Plan Do Check Action system. The source of this research data is the results of interviews with employees of the Sharia Business Unit of Bank SUMUT Medan. The Sharia Business Unit of Bank Sumut Medan has sufficient performance in the benefit process, indicating that the Sharia Business Unit of Bank Sumut Medan provides adequate benefits. Performance results have sufficient benefits. The limitation of this research is the difficulty of deepening the data. Suggestions for subsequent research can deepen data related to measuring the performance of sharia business units.